Risk Factors of Clonally Related, Multi, and Extensively Drug-Resistant Acinetobacter baumannii in Severely Ill COVID-19 Patients - Meqdad Saleh Ahmed; Zirak Faqe Ahmed Abdulrahman; Zanan Mohammed Ameen Taha (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The secondary infection of multi and extensively drug-resistant “Acinetobacter baumannii” in severely ill COVID-19 individuals is usually associated with extended hospitalisation and a high mortality rate. The current study aimed to assess the exact incidence rate of A. baumannii coinfection in severely ill COVID-19 patients admitted to intensive care unit (ICUs), to identify the possible mechanism of A. baumannii transfer to COVID-19 patients and to find out their resistance rate against different antibiotics. Methods. Fifty severely ill “COVID-19” individuals on respiratory support were selected with samples being collected from the pharynx. In addition, another 60 samples were collected from the surrounding environment. Bacterial isolates were diagnosed by microbiological cultures and confirmed by “Vitek 2 system” and real-time PCR. The “Vitek 2 Compact system” was used to evaluate these isolates for antimicrobial susceptibility. The recovered isolates’ DNA fingerprints and genetic similarities were performed using ERIC-PCR. Results.Twenty-six samples were tested positive for A. baumannii (20 out of 50 samples taken from patients, 40%; 6 out of 60 swabs from a nosocomial setting, 10%). All A. baumannii strains isolated from the nosocomial sites were clonally related (have the same genetic lineage) to some strains isolated from patients. However, the majority of the patients’ strains were categorised as belonging to the same genetic lineage. Furthermore, “the multi and extensively drug” resistance patterns were seen in all isolates. In addition, total isolates showed resistance to the most commonly tested antibiotics, while none of them was found to be resistant to tigecycline. Conclusion. Secondary “A. baumannii” infection in severely ill “COVID-19” patients is a serious matter, especially when it has one spot of transmission in the ICU as well as when it is extensively drug-resistant, necessitating an immediate and tactical response to secure the issue.